2000
DOI: 10.1136/bmj.321.7271.1247
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness analysis of intravenous ketorolac and morphine for treating pain after limb injury: double blind randomised controlled trial

Abstract: Objectives To investigate the cost effectiveness of intravenous ketorolac compared with intravenous morphine in relieving pain after blunt limb injury in an accident and emergency department. Design Double blind, randomised, controlled study and cost consequences analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 38 publications
2
51
0
6
Order By: Relevance
“…These results confirm literature recommendations which state that multimodal schemes are more effective for the treatment of PO pain (2,8,(13)(14) . Table 4 shows that, according to scenario 1, the (D) and (E) schemes presented similar effectiveness (43.0%), while the (C) scheme was the worst (33.0%).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…These results confirm literature recommendations which state that multimodal schemes are more effective for the treatment of PO pain (2,8,(13)(14) . Table 4 shows that, according to scenario 1, the (D) and (E) schemes presented similar effectiveness (43.0%), while the (C) scheme was the worst (33.0%).…”
Section: Resultssupporting
confidence: 81%
“…Authors analyzed analgesic therapy in patients with fractured limbs by comparing ketorolac and morphine (8) . for the use of more resources, we must say that the world literature presents a large gap with respect to this topic (9) .…”
Section: Análisis De Costo-efectividad En El Tratamiento Analgésico Pmentioning
confidence: 99%
“…[36][37][38][39][40] Similar results have been found in patients with acute biliary colic and isolated limb injuries and after lithotripsy. [41][42][43][44] Our findings that NSAIDs provided slightly better analgesia with fewer side effects than opioids are in keeping with these studies, although the finding of improved analgesia in patients with renal colic may relate to the local synthesis and release of prostaglandins specific to this condition.…”
Section: Figsupporting
confidence: 76%
“…Studies involving both adults and children with a variety of painful conditions have shown that ibuprofen's efficacy is comparable with or superior to that of opioids. 18,28,32,33 The possibility of comparable efficacy for musculoskeletal pain between NSAIDs and opioids as drug classes is evidenced by other studies that have shown ketorolac to be superior to morphine 34 and equivalent to tramadol. 35 Given ibuprofen's and morphine's similar and inexpensive prices, in addition to these results and ours, ibuprofen should be the initial drug of choice for acutely painful musculoskeletal trauma in children.…”
Section: Discussionmentioning
confidence: 85%